MODERN TRENDS IN INNOVATIVE DEVELOPMENT OF EDUCATIONAL SERVICES FOR FOREIGN CITIZENS IN THE INTEGRATED ENVIRONMENT - I. V. Medynskaya (Дискурс)
The current stage of scientific and technological progress and digital revolution development demonstrates the priority of export of educational services for the increase of foreign policy, foreign economic and cultural relations between countries. This article reviews problems and prospects of innovative development of international scientific and educational collaboration of higher educational institutions in the integrated environment. Strengths and weaknesses of international projects are defined. The study also analyzes the dynamics of the existence of a specific educational service for foreign students on the market. Considering the features of providing innovative educational services in higher educational institutions, an algorithm has been developed and proposed for solving major problems of commercialization of marketing activity functions of foreign citizens recruiting.